2009
DOI: 10.1016/j.bpj.2009.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Novel Micropatterned Cardiac Cell Cultures with Realistic Ventricular Microstructure

Abstract: Systematic studies of cardiac structure-function relationships to date have been hindered by the intrinsic complexity and variability of in vivo and ex vivo model systems. Thus, we set out to develop a reproducible cell culture system that can accurately replicate the realistic microstructure of native cardiac tissues. Using cell micropatterning techniques, we aligned cultured cardiomyocytes at micro- and macroscopic spatial scales to follow local directions of cardiac fibers in murine ventricular cross sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 55 publications
0
78
0
Order By: Relevance
“…Various other methods, such as microcontact printing, electrospinning, and microtopography, have previously been employed to control the structure of engineered cardiac tissue on the microscale [39][40][41] . While these techniques have proven successful in gaining cellular alignment, it is likely that the structure and function of in vivo cardiac tissue is governed by the much smaller, nanotopographical cues of the ECM and thus our NP substrate should prove advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…Various other methods, such as microcontact printing, electrospinning, and microtopography, have previously been employed to control the structure of engineered cardiac tissue on the microscale [39][40][41] . While these techniques have proven successful in gaining cellular alignment, it is likely that the structure and function of in vivo cardiac tissue is governed by the much smaller, nanotopographical cues of the ECM and thus our NP substrate should prove advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…Cell extraction was performed as previously described with some modifications. 21,25,27 Briefly, hearts were extracted from neonatal mice and placed in chilled 1· PBS (calcium magnesium free). Blood was removed by squeezing the ventricles, rinsed with PBS, and placed in HBSS for 10 min.…”
Section: Murine Nncm Isolationmentioning
confidence: 99%
“…15,20 Fabrication of cell culture substrates that mimic the native environment found in the heart may improve the culture conditions of cells for the development of functional cardiac tissue. [21][22][23][24] The alignment of CM has been studied for the last decade using different microfabrication (e.g., microcontact printing, abrasion, photolithography, hot embossing, electrospinning, and laser ablation) approaches. [25][26][27][28][29][30] Studies have also shown that these microtopographic cues have a greater effect on cell alignment than electrical cues.…”
Section: Introductionmentioning
confidence: 99%
“…3 Briefly, coverslips were stained with a voltage sensitive dye (Di-4 ANEPPS, 16 lmol/L) for 5 min, transferred to a custom, thermo-regulated chamber perfused with Tyrodes solution, and stimulated with a platinum bipolar point electrode. Optical signals were recorded by a 504 optical-fiber photodiode array (RedShirt Imaging).…”
Section: Optical Mapping Of Membrane Potentialsmentioning
confidence: 99%
“…Action potential activation times, defined as the times of maximum upstroke, were registered onto the culture's corresponding DTMRI angle map to produce isochrone maps of activation. 3 Local conduction velocities were calculated from activation times and spatially averaged across the entire mapping area as previously described. 3 …”
Section: Optical Mapping Of Membrane Potentialsmentioning
confidence: 99%